1980
DOI: 10.1080/00222895.1980.10735208
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Force and Force Variability in Minimal and Near-Maximal Static and Dynamic Contractions

Abstract: The critical assumption of linearity between force and force variability for rapid movements made by Schmidt, Zelaznik, and Frank (1978) was studied in four experiments in the present study. The first three experiments extended earlier work showing linearity between force and force variability for submaximal force levels in static and dynamic contractions. However, at near-maximal force levels, when force was increased, force variability leveled off and then decreased in both static and dynamic conditions. A f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
62
0
3

Year Published

1985
1985
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 5 publications
16
62
0
3
Order By: Relevance
“…6a and c, is a commonly accepted fact, both in isometric and in isotonic studies. This fundamental phenomenon has been reported for peak velocity (Gielen et al 1985;Nagasaki 1989), peak acceleration (Carlton and Newell 1988; Gielen et al 1985), peak isotonic force (Carlton and Newell 1988), peak isometric force Sherwood and Schmidt 1980), peak first and second time derivative of the isometric force ) and peak torque (Carlton and Newell 1988). Such general behavior is not surprising in the context of the kinematic theory since it is always the same neuromuscular synergy that is investigated and since a single basic law (1) is sufficient to describe its general behavior under a number of conditions.…”
Section: Variability Analysis and Predictionsmentioning
confidence: 85%
“…6a and c, is a commonly accepted fact, both in isometric and in isotonic studies. This fundamental phenomenon has been reported for peak velocity (Gielen et al 1985;Nagasaki 1989), peak acceleration (Carlton and Newell 1988; Gielen et al 1985), peak isotonic force (Carlton and Newell 1988), peak isometric force Sherwood and Schmidt 1980), peak first and second time derivative of the isometric force ) and peak torque (Carlton and Newell 1988). Such general behavior is not surprising in the context of the kinematic theory since it is always the same neuromuscular synergy that is investigated and since a single basic law (1) is sufficient to describe its general behavior under a number of conditions.…”
Section: Variability Analysis and Predictionsmentioning
confidence: 85%
“…An increase in positional variability during movements performed as fast as possible with an increase in movement distance has been described in many studies and is considered an example of the speed-accuracy trade-off (Schmidt et al 1978(Schmidt et al , 1979Sherwood and Schmidt 1980;Wright and Meyer 1983; although see Latash and Gottlieb 1990). In all these studies, positional variability was assessed at the alleged time of movement termination.…”
Section: The Speed-accuracy Trade-offmentioning
confidence: 95%
“…However, such a dependence still exists at later times as well. Let us note that in many studies, movements were considered stopped and measurements were made at a moment of touching the target (Schmidt et al 1978(Schmidt et al , 1979Sherwood and Schmidt 1980;Sherwood et al 1988). The velocity of the endpoint at the moment of impact was presumably not zero.…”
Section: The Speed-accuracy Trade-offmentioning
confidence: 99%
“…(Below, we shall argue that, even at this level, Plamondon & Alimi's [P&A's] account is flawed). The level of movement execution can contribute to other types of trade-offs, for example to the scaling of the standard deviation of final position with movement distance and time (Schmidt et al 1979;Sherwood & Schmidt 1980). Thus, P&A's account fails to distinguish between these distinct forms of trade-offs and analyzes them erroneously as a single phenomenon.…”
Section: Importance Of Individual Datamentioning
confidence: 99%
“…Most of the detailed studies have reported nonproportional relationships between force and force variability in both isometric (Carlton & Newell 1985;Fullerton & Cattell 1892;Jenkins 1947;Newell & Carlton 1985;Noble & Bahrick 1956;Provins 1957) and anisometric tasks (Newell et al 1982). Furthermore, this relationship was found to have an inverted U shape Sherwood & Schmidt 1980;Sherwood et al 1988).…”
Section: Movements With Temporal Constraints Where Mt Is Given: Focumentioning
confidence: 99%